2007
DOI: 10.1128/jcm.02592-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology ofMycobacterium abscessus, with Focus on Cystic Fibrosis

Abstract: Mycobacterium abscessus has been isolated increasingly often from the respiratory tracts of cystic fibrosis (CF) patients. It is not known whether these organisms are transmitted from person to person or acquired from environmental sources. Here, colony morphology and pulsed-field gel electrophoresis (PFGE) pattern were examined for 71 isolates of M. abscessus derived from 14 CF patients, three non-CF patients with chronic respiratory M. abscessus infection or colonization, one patient with mastoiditis, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(190 citation statements)
references
References 42 publications
(32 reference statements)
6
182
0
2
Order By: Relevance
“…The emergence of MABSC in CF patients is estimated to have occurred in the mid-1990s [35] and was probably multifactorial. This period saw major improvements in the microbiological methods for isolating MABSC and other NTM [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of MABSC in CF patients is estimated to have occurred in the mid-1990s [35] and was probably multifactorial. This period saw major improvements in the microbiological methods for isolating MABSC and other NTM [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…102 Among 14 NTMinfected individuals with CF included in a study in Sweden, a shared strain was found only in 1 pair of siblings. 228 However, a recent report from the United States described the use of rep-PCR and PFGE typing to show the apparent spread of a strain of M. abscessus subsp. massiliense from a chronically infected adult with CF to 4 others attending the same clinic in Seattle.…”
Section: Iiia5 Nontuberculous Mycobacteriamentioning
confidence: 99%
“…M. abscessus lung disease is highly prevalent in patients with cystic fibrosis (CF) and is becoming a major issue for most CF centers worldwide (3)(4)(5)(6). Although M. abscessus is an RGM, it can persist and cause lung disease with caseous lesions (7).…”
mentioning
confidence: 99%